Prospecção e caracterização de genes associados ao processo de indução floral em cana-de-açúcar - Furtado, Cristiane Miranda (2007)
The northeastern region is responsible to 14.32% of sugarcane national production. This lowered contribution is due to edaphoclimatic condition. Flowering is a vital process to plant which consumes lots of energy and it culminates in a process called isoporization. This one can give in a decreasing of 60% on alcohol and water production. It may consider that cropped sugarcane has a hibrid with octaploid genome, there are varieties with a flowering standard until of non flowering. Using this natural genetic potential on different croppings of sugarcane, the aim of this work was to understand as this process occurs by the usage of subtractive approaches. The total RNA was extracted using Trizol of peaks of merisematics of croppings with induced flowering and other with late flowering. From this total RNA were built four subtractives libraries (B1- induced early flowering subtracted on late flowering not induced; B2- late flowering not induced subtracted induced early flowering; B3- induced early flowering subtracted of not induced early flowering; B02- not induced early flowering subtracted from induced early flowering) using kits Super Smart cDNA synthesis and BD Clontech kit select cDNA subtraction (Clontech). This material was clone don vector pGEM T-easy(Promega) and changed in competent cells of E.coli DH10B. Given analysis sequence was carried out a program BLASTn against database of NCBI and genome of Arabidopsis thaliana, rice and maize. Clones were grouped in 9 different classes according to function. Some factors already related as couples of flower induction were identified at different libraries. And grouped proteins with cell cycle and it controls were presents, mainly kinases proteins. Related factors to proteic sinthesis, metabolism, defence, cell communication were also given in both libraries .Some identified genes did not show similarity on database or homology with hypothesis function, and it can represents new genes to be deposited in international database. These results offers that some identified on sugarcane, classified as on factors classes, cell cycle and cell communication, trough unknown genes, can be linked with genetic changing to the flowering process found in the northeastern region